Contrasting influences of seasonal and intra-seasonal hydroclimatic variabilities on the irrigated rice paddies of Northern Peninsular Malaysia for weather index insurance design - Zulkafli, Zed Diyana; Muharam, Farrah Melissa; Raffar, Nurfarhana; Jajarmizadeh, Amirparsa; Abdi, Mukhtar Jibril; Mohamed Rehan, Balqis; Khairudin, Nurulhuda (Multidisciplinary Digital Publishing Institute, 2021)
Good index selection is key to minimising basis risk in weather index insurance design. However, interannual, seasonal, and intra-seasonal hydroclimatic variabilities pose challenges in identifying robust proxies for crop losses. In this study, we systematically investigated 574 hydroclimatic indices for their relationships with yield in Malaysia’s irrigated double planting system, using the Muda rice granary as a case study. The responses of seasonal rice yields to seasonal and monthly averages and to extreme rainfall, temperature, and streamflow statistics from 16 years’ observations were examined by using correlation analysis and linear regression. We found that the minimum temperature during the crop flowering to the maturity phase governed yield in the drier off-season (season 1, March to July, Pearson correlation, r = +0.87; coefficient of determination, R2 = 74%). In contrast, the average streamflow during the crop maturity phase regulated yield in the main planting season (season 2, September to January, r = +0.82, R2 = 67%). During the respective periods, these indices were at their lowest in the seasons. Based on these findings, we recommend temperature- and water-supply-based indices as the foundations for developing insurance contracts for the rice system in northern Peninsular Malaysia.